(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The question is solved in the article what to evaluate connection with specialty of the subjects of informatics. The course descriptions are given in the internet. The authors offer variant what evaluate course descriptions by 3 score system. The lecturers’ produced materials show more demonstrative connection with specialty. The authors show what we need regard evaluating and offer evaluation methodic by 5 score system. The criterions are offered what to evaluate if methodic works right. The viewpoint based with research between students.